Best practice for achieving real-time virtual reality architectural visualization: Achieving virtual reality presentation performance efficiency - Chung, D.H.J. (2013)
CAADRIA 2007 - The Association for Computer-Aided Architectural Design Research in Asia: Digitization and Globalization